PENGARUH RETURN ON ASSET DAN DEBT TO ASSET RATIO TERHADAP PERTUMBUHAN LABA PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2014-2023 - Achmad Haryanto; Intan Sari Budhiarjo (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of  the ratio of Return On Asset (ROA)  and Debt To Asset Ratio (DAR) to the Profit Growth of PT Indofood Sukses Makmur Tbk for the 2014-2023 Periode. The research methodology used is associative quantitative research. The population of this study is the financial report of PT Indofood Sukses Makmur for the period 2014-2023 with the sample taken, namely the financial statements for 2014-2023. The data analysis method used descriptive statistical analysis tests, classical assumption tests, multiple linear regression tests, hopitesis tests and determination coefficient tests with the help of the SPSS version 25 program. The independent variables consist of Return On Asset (X1) and Debt To Asset Ratio (X2), while the dependent variable is Profit Growth. The results of the t-test showed that the tcount value was 4.045 > ttable 2.36462 and the sig. 0.005 < 0.05. This means that the Return On Asset variable partially has a significant influence on Profit Growth. Then the Debt To Asset Ratio variable shows a calculated value of 2.091 < a table of 2.36462 and a value of sig. 0.075 > 0.05. This means that the Debt To Asset Ratio variable has no influence and is not significant to Profit Growth. And simultaneously (f-test) showed that the value of fcal 8.1877 > ftable 4.74 and the value of sig. 0.015 < 0.05, this means that the Return On Asset and Debt To Asset Ratio variables have a significant influence on Profit Growth